Testing Corporate Finance and Signaling Theory in Indonesia’s Property Sector: ROA, TATO, and Firm Size Effects on Firm Value - Seda, Savira S; Kartono, Kartono (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study examines the impact of Return on Assets (ROA), Total Asset Turnover (TATO), and Firm Size on corporate value, highlighting its importance for investors and shareholders. Using a descriptive quantitative approach, data were collected from PT Ciputra Development Tbk’s annual financial statements for 2015–2024 and analyzed with multiple linear regression. The results show that ROA and TATO individually do not significantly influence corporate value, while Firm Size has a significant negative effect. However, when considered together, ROA, TATO, and Firm Size collectively have a significant impact. This indicates that although single financial indicators may be less influential, their combined effect is substantial. The study underscores that investors should assess these variables collectively rather than separately to make informed decisions, emphasizing the need for a comprehensive evaluation of financial performance factors in determining corporate value.